Apelin Serum Level in Egyptian Patients with Chronic Hepatitis C - Hala O. El-Mesallamy; Nadia M. Hamdy; Hanan H. Rizk; Abdel-Rahman El-Zayadi (Mediators of Inflammation)
Objective. Highlighting the apelin system would present a new therapeutic target for liver disease. Apelin; endogenous ligand for the orphan receptor APJ, was recently suggested to be associated with fibrosis progression and cirrhosis in addition to insulin resistance (IR) and inflammation. The present study was conducted to evaluate blood apelin level changes among 73 chronic hepatitis C (CHC) Egyptian patients and if associated with body mass index (BMI), IR, and tumor necrosis factor-alpha (TNF-α). Serum apelin levels were significantly higher in patients with CHC with median value (3.25) when compared with controls (1.11), at P<0.0001, with significant apelin variations among asymptomatic carriers (ASC), fibrosis, and cirrhosis patients, and also among obese and nonobese patients. Multiple regression analysis depicted that BMI, triglycerides, and total cholesterol were independent correlation factors to apelin levels, whereas TNF-α was found to be significantly negatively correlated to adjusted apelin in CHC patients (r=−0.5944, P<0.0001). IR was positively correlated to adjusted apelin in CHC patients (r=0.2663, P<0.05). Conclusion. Apelin level varies among stages of CHC, which may contribute to fibrosis progression. In addition, obesity and IR could act as comorbid factors affecting apelin level in patients with CHC.